Knowledge on Chemical Pesticide use among Farmers Exposed to Pesticides in Panchkhal Municipality, Kavrepalanchok, Nepal - Leela Paudel; Rajendra Neupane; Lochana Shrestha; Lee Budhathoki; Keshav Raj Paudel (Hindawi Limited, 2024)
Background. Pesticide exposure is a serious threat to public health in developing countries like Nepal. As an agricultural country, farmers are using pesticides indiscriminately to increase the yield of crops, which results in continued contamination of the environment and food and has adverse effects on human health. This study aims to assess the knowledge and evaluate the relationship between pesticide use knowledge and pesticide toxicity symptoms among farmers in Panchkhal Municipality. Materials and Methods. A cross-sectional study design was used among 238 farmers (both male and female) exposed to pesticides for a minimum of 1 year. The data collection period was from April to June 2022. The data were collected using convenient sampling through interviews. Semistructured questionnaires were used as a tool for data collection. This study has been approved by the ethics committee. Data entry and analysis were done in SPSS version 16.00. Bivariate analysis was done using the Chi-square test. Results. The mean age ± SD of the participants was 45.75 ± 13.12 years. The mean year of exposure was 15.52 ± 9.46 years, and the mean duration of working in the field was 3.22 ± 2.17 hr/day. Burning eye (51.2%) was the most common symptom of pesticide poisoning. The most common pesticide used was insecticide. Most farmers (92.4%) had good knowledge of the use of pesticides. There was no significant association between the symptoms of pesticide exposure and knowledge. Those who stored the pesticide properly in a locked container in a well-ventilated area showed a significant association with knowledge of pesticide use (P≤0.001). Conclusion. This study showed that most farmers have good knowledge of pesticide use. Still, educational programs and legislation promoting the use of safer pesticides are needed because they are the ones who handle and use chemical pesticides. Furthermore, the government should conduct training on the safe management of pesticide use.